2021
DOI: 10.1038/s41438-021-00490-6
|View full text |Cite|
|
Sign up to set email alerts
|

The chromosome-based lavender genome provides new insights into Lamiaceae evolution and terpenoid biosynthesis

Abstract: The aromatic shrub Lavandula angustifolia produces various volatile terpenoids that serve as resources for essential oils and function in plant-insect communication. To better understand the genetic basis of the terpenoid diversity in lavender, we present a high-quality reference genome for the Chinese lavender cultivar “Jingxun 2” using PacBio and Hi-C technologies to anchor the 894.50 Mb genome assembly into 27 pseudochromosomes. In addition to the γ triplication event, lavender underwent two rounds of whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…We identified 20/21 TPS genes in D. turbinatus and H. hainanensis , respectively (Figure 5a and Additional file 1: Figure S7), which did not exhibit a remarkable difference in TPS number compared with other selected plants (Additional file 2: Table S10). Similar to previous results in other plants (Xu et al ., 2020; Li, Wang, et al ., 2021), many TPS genes in D. turbinatus and H. hainanensis also exhibited a tandem array, and these genes formed TPS gene clusters on chromosomes 4, 8, 10 and 1, 7 (Figure 5b and Additional file 1: Figure S8), suggesting these genes underwent recent tandem duplication events.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 20/21 TPS genes in D. turbinatus and H. hainanensis , respectively (Figure 5a and Additional file 1: Figure S7), which did not exhibit a remarkable difference in TPS number compared with other selected plants (Additional file 2: Table S10). Similar to previous results in other plants (Xu et al ., 2020; Li, Wang, et al ., 2021), many TPS genes in D. turbinatus and H. hainanensis also exhibited a tandem array, and these genes formed TPS gene clusters on chromosomes 4, 8, 10 and 1, 7 (Figure 5b and Additional file 1: Figure S8), suggesting these genes underwent recent tandem duplication events.…”
Section: Resultsmentioning
confidence: 99%
“…In citrus, a total of 55 CsTPS genes have been identified, and seven TPS genes are related to sesquiterpene biosynthesis, including one related to β-farnesene biosynthesis and two related to β-caryophyllene biosynthesis (Alquézar et al, 2017). More recently, 52 TPS family genes have been identified in wintersweet (Chimonanthus praecox), indicating a possible mechanism for the formation of flower aroma (Shang et al, 2020), while 100 TPS genes have been found in the lavender genome (Li et al, 2021). Here, the identification of 34 TPS genes in the red bayberry genome (Supplementary Table 7), much less than those in the genomes mentioned above, supports red bayberry not having had a whole genome duplication event (Jia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the D. carota and A. graveolens that belonged to Apiaceae, one shared WGD occurred in about 43 Mya, and one recent WGD only existed in A. graveolens in approximately 1.9 Mya, and this duplication contributed to the expansion of terpene synthase gene families ( Song X. et al, 2020 ). The second branch in the eudicots part includes six plants belonging to Lamiales, one shared WGD (almost 60.7 Mya) was identified in S. baicalensis , S. barbata , S. miltiorrhiza , and S. indicum , which might be responsible for chromosomal expansion and rearrangement ( Xu et al, 2020a ), and two rounds of WGD were found in S. splendens and L. angustifolia , which could result in the gene families expansion related to terpenoid biosynthesis ( Li et al, 2021 ). In P. cuspidatum , it experienced current lineage-specific WGD at 6.6 Mya after the divergence with F. tataricum from the ancestor, and it shared the ancient and common WGD with F. tataricum at 65 Mya ( Zhang Y. et al, 2019 ), after this WGD, the genome of F. tataricum experienced dramatic chromosomal rearrangements, resulting in very fragmented intra-genome collinear blocks ( Zhang L. et al, 2017 ).…”
Section: Application Of Medicinal Plant Genomesmentioning
confidence: 99%